Seismic performance of dry-assembled cold-formed steel-foam concrete composite shear walls with flanges - Peng, Zhiming; Ding, Xiaomeng; Xu, Zhifeng; Chen, Zhongfan; Lin, Jiankang (Thin-walled structures, 2025)
•Introduced a novel dry-assembled flanged CFS-foam concrete composite shear wall.•Quantified seismic performance via quasi-static tests and FEM validation.•Developed flange-web interaction model revealing load-transfer mechanisms.•Established shear capacity formula quantifying component contributions.•Proposed restoring force model with pinching and stiffness degradation effects. This study proposes a novel dry connection method for prefabricated cold-formed steel (CFS) wall flanges and webs, aiming to improve construction efficiency. Six full-scale prefabricated H-shaped CFS-foam concrete composite shear walls (PCFS-FCSWs) were tested under quasi-static cyclic loading to evaluate the influence of foam concrete infill, magnesium oxide (MgO) board configuration (single- or double-sided), aspect ratio, flange width, and vertical load on seismic performance. The results demonstrate that PCFS-FCSWs exhibit superior seismic performance, with primary failure modes involving MgO board tearing, horizontal bracing buckling, and foam concrete crushing. The web resisted approximately 70 % of the lateral shear force, with foam concrete contributing 40 %. The MgO boards’ skin effect primarily governed lateral resistance in the cavity wall, while the CFS frame contributed only about 10 %. Reducing the aspect ratio increased shear capacity but decreased ductility. Increasing flange width enhanced seismic performance, but the improvement plateaued beyond 600 mm. A refined ABAQUS finite element model (FEM) accurately replicated experimental failure modes and revealed a diagonal compression strut mechanism in the foam concrete web. Based on the superposition principle, a shear capacity formula was derived, and a restoring force model was established for hysteretic behavior prediction. Theoretical results agreed well with experiments, providing valuable insights for the engineering design of dry-assembled flanged CFS composite walls.